EPIDEMIOLOGICAL AND PSYCHOSOCIAL ASSESSMENT OF CHILDHOOD OBESITY - PROSPECTIVE STUDY - Oana Elena Iaru; Raluca Maria Vlad; Marina Popov; Roxana Andrei; Irina Dijmarescu; Daniela Pacurar; Dumitru Oraseanu (Amaltea Medical Publishing House, 2016)
Objective. The aim of this study was the evaluation of epidemiological and psychosocial parameters in a sample of overweight and obese children hospitalized for various pathologies. The duration of the study was 12 months. Methods. We performed a prospective study that included overweight and obese children admitted in the Paediatric Unit of our hospital from July 2014 until June 2015. The exclusion criteria consisted of the presence of secondary pathologies related to obesity. A questionnaire was applied to all patients included with questions about family and personal risk factors for obesity; we realised also a psychological evaluation and quality of life assessment (PedsQL). For each patient we performed clinical evaluation, laboratory and imaging investigations (abdominal ultrasound). Results. The study included 78 patients: 27 overweight (34.6%), 51 obese (65.3%). We studied the family history concerning the weight status: 55 had one obese parent and 15 had both parents with obesity. We identified dietary errors for almost all patients (65 patients = 83.3%). The average number of hours of physical activity was rather low (0.57 hours/day) and the average time spent in front of the TV and computer was increased (5.7 hours/day). Conclusions. Obesity has been associated with familial background of obesity, dietary errors (both eating schedule and composition), decreased time spent doing physical activity and increased time dedicated to computer and television. These conclusions should be considered in the prophylactic and curative programs done for this pathology.